Digital Evidence And Its Challenges In Indonesian Civil Law - Sunardi, Heru; Jamaludin, Jamaludin; Moh. Asyiq Amrulloh; Dewi Hikmayatun Ulya (Journal of Law, Politic and Humanities, 2026)
Abstract This research was conducted with the aim of finding out the legal basis, challenges and legal solutions faced in digital evidence in electronic contract disputes in Indonesia. The type of research used in this research is normative legal research using statutory and conceptual approaches. The results of this research show that: 1) The legal basis for digital proof of electronic contract disputes is regulated in the ITE Law and the Civil Code. The ITE Law is regulated in Article 1 paragraph (17) and Article 5 paragraph (1). Meanwhile, the Civil Code is regulated in Article 1320, Article 1338 and Article 1866 of the Civil Code. 2) The challenges of digital proof of electronic contract disputes include three aspects, namely: The judicial aspect (judges are still hesitant in considering authentic electronic documents as valid evidence), the technical aspect (it is difficult to guarantee the authenticity of data without special expertise), and the legal aspect (there are no formal rules in civil procedural law regarding procedures for electronic proof). The solutions that can be implemented are by strengthening the capacity and technical guidelines for law enforcement officials, strategic efforts are needed to ensure the authentication, integrity and reliability of electronic evidence presented at trial, as well as reformulating civil procedural law and harmonizing other regulations relating to electronic evidence.